Impact of sacubitril/valsartan on echo parameters in heart failure patients with reduced ejection fraction a prospective evaluation. (December 2019) - Bayard, Geoffrey; Da Costa, Antoine; Pierrard, Romain; Roméyer-Bouchard, Cécile; Guichard, Jean Baptiste; Isaaz, Karl
Abstract: Background: Sacubitril/valsartan has been shown to improve mortality and reduce hospitalizations in patients with heart failure (HF) with reduced ejection fraction (HFrEF). Although the physiological action mechanisms of sacubitril/valsartan are well described, its effects on left ventricular (LV) remodelling and other echocardiographic (echo) parameters have not been prospectively studied. Objective: The aim of this prospective study was to: McMurray et al. (2012) [1 ] evaluate if sacubitril/valsartan impacts LV remodelling based on echo parameters; Ponikowski et al. (2016) [2 ] identify the predictive factors of sacubitril/valsartan response or intolerance. Methods: From May 2017 to September 2018, 52 HF patients were prospectively enrolled using PARADIGM-HF criteria: Class II, III, or IV HF; ejection fraction (EF) of 40% or less; hospitalized for HF within the previous 12 months. Echo evaluation was performed before initiating sacubitril/valsartan and 3 months after optimal dose adjustment. Based on previous studies, patients with (absolute) improvement in left ventricular ejection fraction (LVEF) ≥ 5% were considered significant sacubitril/valsartan responders. Results: The 52 patients completing the study were characterized by age: 70 ± 10 years; gender: 11women; aetiology: idiopathic in 20 and ischaemic in 32; NYHA Class: II in 17 and III in 35; LVEF: 32 ± 5%; NTProBNP: 1805 ± 1914 pg/mL. The final population comprised 41 pts (79%), as 11 (21%) did not tolerate sacubitril/valsartan therapy. Under sacubitril/valsartan, several echo parameters significantly improved: LVEF from 32.6 ± 5 to 36 ± 6% ( p  < 0.0001); LVES volume from 117 ± 40 to 108 ± 46 mL ( p  = 0.0051); SEV from 59 ± 12 to 64 ± 13 ( p  = 0.0061); LVEDD from 60 ± 4 to 57 ± 5 mm ( p  = 0.0002); mean right ventricular systolic pressure (RVSP) from 39 ± 10 to 32 ± 8 ( p  = 0.0001). No significant modifications were observed concerning LV diastolic parameters or RV echo parameters. Sacubitril/valsartan echo responders (n = 18/41; 42%) had less severe LV remodelling, as shown by LVEDV: 144 ± 37 vs. 193 ± 47 mL, p  = 0.0009; LVESV: 96 ± 28 vs. 133 ± 42 mL; p  = 0.003; LVTDD: 61 ± 4 vs. 57 ± 5 mm; p  = 0.02; significant mitral regurgitation: 6/18 (33%) vs. 16/23 (69%), p  = 0.02; no diastolic LV or RV parameters impacted sacubitril/valsartan response. Predictors of sacubitril/valsartan intolerance were baseline creatinine level: 137 ± 99 vs. 100 ± 24, p  = 0.03; LVEF: 29 ± 6 vs. 33 ± 5%; p  = 0.04. Conclusions: In HFrEF patients, sacubitril/valsartan significantly improves LV systolic remodelling, without any significant effects on LV diastolic or RV systolic echo parameters. Sacubitril/valsartan responders exhibit both less severe LV remodelling and less significant mitral regurgitation. Accordingly, sacubitril/valsartan could be used as soon as possible in HFrEF patients in order to limit LV remodelling, while precluding non-response or intolerance. Highlights: Patients with HFeEF under sacubitril/valsartan improve significantly the LV systolic remodelling. Responders to sacubitril/valsartan have both less severe LV remodelling and less significant mitral regurgitation Sacubitril/valsartan may be used as soon as possible in patients with HFrEF in order to limit the LV remodelling and preclude non-response or intolerance.